Combinatorial Portfolio Selection with the ELECTRE III method: Case study of the Stock Exchange of Thailand (SET) - Veera Boonjing; Laor Boongasame (My University, 2016)
Various techniques of portfolio selection are applied to interpret the status of the market and predict the market's future trend, but they are not beneficial to small investors because these techniques should be administered by an expert.In addition, these techniques desire accumulation of data about the market and complicated calculations, which is too much effort for individual small investors.Therefore, portfolio selection with two significant financial ratios using the ELECTRE III method is proposed for these investors to make trading decisions.In order to demonstrate the effectiveness of this new method, it is compared to the situation where a fix percentage allocation existed and data was collected from the Stock Exchange of Thailand (SET).
Keywords: ELECTRE; Stock Market Forecasting Methods